2009
DOI: 10.1016/j.brainres.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on load-dependent brain activations in working memory for novel material

Abstract: Three competing models of cognitive aging (neural compensation, capacity limitations, neural inefficiency) were examined in relation to working memory for novel non-verbal material. To accomplish this goal young (n=25) and old (n=25) participants performed a delayed item recognition (DIR) task while being scanned with bold fMRI. The stimuli in the DIR task consisted of computergenerated closed-curve shapes with each shape presented only once in the testing conditions of each participant. This ensured that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 91 publications
6
45
1
Order By: Relevance
“…These timing differences, as well as the use of partial trials in the present study to improve signal deconvolution, may account for the difference in results between our study and the study by Cappell et al (2010). With regard to our finding of aging effects in the encoding phase, but not in the maintenance phase, several previous studies have also reported differences in the effects of aging across the encoding, maintenance and retrieval phases of WM tasks, indicating that age-related activation changes can vary depending on the cognitive process engaged (Carp, Gmeindl, & Reuter-Lorenz, 2010;Holtzer et al, 2009;Rypma & D'Esposito, 2000;Zarahn et al, 2007). Interestingly, despite equivalent education level and employment type in the two age groups, middle-aged adults were characterized by near-significantly higher letter fluency scores and significantly higher Dutch adult reading test scores.…”
Section: Discussioncontrasting
confidence: 59%
“…These timing differences, as well as the use of partial trials in the present study to improve signal deconvolution, may account for the difference in results between our study and the study by Cappell et al (2010). With regard to our finding of aging effects in the encoding phase, but not in the maintenance phase, several previous studies have also reported differences in the effects of aging across the encoding, maintenance and retrieval phases of WM tasks, indicating that age-related activation changes can vary depending on the cognitive process engaged (Carp, Gmeindl, & Reuter-Lorenz, 2010;Holtzer et al, 2009;Rypma & D'Esposito, 2000;Zarahn et al, 2007). Interestingly, despite equivalent education level and employment type in the two age groups, middle-aged adults were characterized by near-significantly higher letter fluency scores and significantly higher Dutch adult reading test scores.…”
Section: Discussioncontrasting
confidence: 59%
“…Specifically, the observed relationship suggests that young adults were able to boost activation when the task became more challenging and engage in more extensive stimulus processing, which may have supported their superior performance at the higher set sizes. Greater neural capacity (here defined as higher network expression at higher levels of task demand) in young compared to older adults has been described previously (e.g., Cappell et al, 2010; Holtzer et al, 2009; Stern et al, 2012). The biological basis of this age-related capacity difference is currently not known, but may be related to differences in neural connectivity and plasticity (Burke and Barnes, 2006), white matter integrity (e.g., Bennett and Rypma, 2013), or brain oxygen metabolism (Hutchison et al, 2012) that manifest with aging.…”
Section: Discussionmentioning
confidence: 58%
“…Age is one of the most studied characteristics to delineate a possible impact on working memory processes [6]. A downward trajectory across the adult life span in nondemented individuals in working memory has been previously reported [7]; however, a long-standing controversy in the working memory aging literature roots questions whether the effects of aging on various cognitive functions have the same common cause or several different causes. Age-related decreases in occipital cortex activity have been attributed to inefficient sensory processing in the ventral (occipito-temporal) pathway.…”
Section: Introductionmentioning
confidence: 99%